The effect of assessment form to the ability of student to answer the problem correctly - Arifian Dimas; Cari Cari; Suparmi Suparmi; Jeffry Handhika (Universitas Sebelas Maret, 2017)
Assessment is an important part of education. For educators, are collecting information about students learning and information about the learning process. For students, the assessment is the process of informing them about the progress of learning. Effective assessment process is responsive to the strengths, needs and clearly articulated student learning objectives. This research was aimed to know the effect of assessment form towards students ability in answering the problem correctly on kinematics and dynamics of motion. The method used in this research is descriptive qualitative. The data collecting method are assessment test and interview. Assessment test instrument are written test and animation form test. The question we use was taken